LINGUISTIC FEATURES OF EUPHEMISMS IN ENGLISH AND UZBEK LANGUAGES (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
The article discusses the discursive characteristics of euphemisms, their role in comparative languages, their study, and general classification. It also focuses on linguists’ scientific and theoretical perspectives on euphemisms, summarizing their distinctive features.